Towards an environmental community. Walter Benjamin and the shift from the human domination of nature to the domination of the relationship itself (Lebenswelt. Aesthetics and philosophy of experience., 2025)
In a time of transition and danger, where environmental transformations merge with essential and irreversible changes, the debate requires and would benefit from new philosophical definitions. Revisiting Walter Benjamin’s work can provide valuable insights also into rethinking human-centredness and its relationship with the environment around. Therefore, reconstructing and actualising Benjamin’s thought can contribute to re-discussing the relationship with, and control over, nature. This can be achieved by analysing key themes such as progress, technology, and the relationship between humans and nature.Benjamin’s leitmotif of the critique of quantitative progress, which is central to his transversal approach to reading modernity and contemporaneity, also form the basis of this topic. Unlike the so-called modern approach, he suggests a conception in which the production of knowledge is reciprocal rather than hierarchical. The modern knowing subject should thus adopt a non-dominating approach when interacting whit what they call nature. This would also prevent them from falling into the dangerous cycle of capitalism, growth and destruction.The modern perspective, which is based on the assumption that humans and nature are distinct entities, with humans dominating nature, critiques traditional anthropocentrism. It suggests a shift in epistemology, in which nature becomes an integral part of a collective and inclusive cognitive process. This shift can be seen as the passage from the domination over something – in this case, nature – to the domination of the relational category itself (in One-Way Street: Benjamin 2016, 95), and points towards what we may term a horizontal environmental community.At the same time, and more classically, Benjamin’s work serves as a warning against the dangers inherent in 20th-century technology and politics. While doing so, it also highlights more general dynamics, whose risks include environmental destruction and political conformism. His critical reflections on technology and political limits – before annihilation and destruction – resonate with current concerns about sustainability and ecology, demonstrating foresight regarding these now widespread thoughts on these issues.With this lesser-travelled path of his thought, this article aims to fill a gap, contributing to both historiographical and philosophical reconstruction, as well as to current debates, by positing that Benjamin articulates these concerns in terms of sustainability and post-anthropocentrism – albeit using different terminology.